Conceptualising the Connectivity Between Human Behavior and Diversity Management in Schools - Adeoye, Moses Adeleke; Bolaji, Oluwafemi Tajudeen (Bumi Publikasi Nusantara, 2023)
It is impossible to prevent diversity in the educational system because students come from a variety of racial, ethnic, religious, and other cultural backgrounds. As a means of fostering an inclusive and varied workplace, diversity management is gradually becoming more popular. Such approaches have a significant impact on organizational performance when they are applied effectively. The purpose of the survey design was to determine how much employee work attitudes, which are influenced by diversity management, affect organizational effectiveness. A conceptual literature review was reviewed to ascertain the connectivity between diversity management and human behavior. Ageism, aversion to change, and gender discrimination are the three main obstacles to workplace diversity according to empirical evidence. A person's behavior is a result of how they interact with their environment, according to the interactionist viewpoint. The idea of managing diversity acknowledges the advantages due to two factors brought about by successful diversity management increased cognitive flexibility and higher organizational flexibility in terms of processes, openness to new ideas, and ability to handle change. The study concluded that successfully managing diversity can lead to more committed, better satisfied, better performing employees and potentially better financial performance for an organization. It was recommended among others that periodic training on diversity and diversity management is required for all employees to know the importance of diversity in an organization.